Handling Device Addiction in Children Aged 6-12 Years in The Village Environment of Si Lebo-Lebo - Novika Danisa (Journal of Community Service For Indonesian Society, 2023)
This service is carried out in Si lebo-lebo Village using a qualitative approach. This study uses a qualitative approach as an approach or search to explore and understand a central phenomenon. The results of qualitative research in the realm of education are descriptive. The research subjects used in this study were several students in Si lebo-lebo Village. The sample collection technique used is sample random sampling, which means that each member of the population has the same opportunity and opportunity to become the research sample. Children must be accustomed to doing other positive things to distract children from playing cellphones. One of the things that can be done is with tutoring, unfortunately children are now reluctant to learn, because they are addicted to gadgets. Therefore, by holding tutoring in the village, the children can reduce their screen time, besides that the children also become socialized with other children. It's just that the learning supervisors have to look for new innovations to be able to survive and be able to continue to divert children to remember the games that are on the device. Parents must also play an important role in the success of the program to reduce screentime in children. This program was created with the aim of reducing the percentage of children's addiction to playing cellphones. It's just that the learning supervisors have to look for new innovations to be able to survive and be able to continue to divert children to remember the games that are on the device. Parents must also play an important role in the success of the program to reduce screentime in children. This program was created with the aim of reducing the percentage of children's addiction to playing cellphones. It's just that the learning supervisors have to look for new innovations to be able to survive and be able to continue to divert children to remember the games that are on the device. Parents must also play an important role in the success of the program to reduce screentime in children. This program was created with the aim of reducing the percentage of children's addiction to playing cellphones.This work program is a work program that has been prepared and planned in advance before the implementation of the activity.